Forecast analysis of the impact of remote workers visa policy on the resilience of the tourism economy: A geographical and economic perspective - Noviarini, Nurina; Samputra, Palupi Lindiasari (Economic Military and Geographically Business Review, 2025)
Background: The tourism sector is most vulnerable to economic risk due to the impact of the COVID-19 pandemic in Bali. As a continuation of the discourse on a particular digital nomad visa in 2022, the Remote Worker Visa is designed to mitigate economic risk. This study aims to analyze the impact of the Indonesian Remote Workers Visa on regional economic resilience in the tourism sector. Methods: This study uses a Delphi analysis approach consisting of two stages: a qualitative method with expert interview techniques and a quantitative method with a questionnaire technique. Findings: The results of the analysis are based on the results of the consensus of expert sources with standard deviation parameters (<1.5) and Interquartile (<2.5). Seven expert sources were from the Ministry of Tourism and Creative Economy and academics. The study results show that the tourism sector in Bali has not fully recovered even though there is a remote worker visa, and regional economic resilience has not been able to pass the recovery phase. Conclusion: The tourism sector is said to be able to avoid losses (vulnerability, resilience, and resilience) from the impact of the COVID-19 pandemic with the support of remote worker visas. Novelty/Originality of this article: This study provides a novel analysis of the Indonesian Remote Worker Visa’s impact on Bali’s tourism resilience, using Delphi analysis to assess its effectiveness in mitigating post-pandemic economic risks.